Talent Management Research in a VUCA World: A Bibliometric and Systematic Literature Review - Firdaus, Riska; Yunus, Muhammad; Rusdi, Muhammad; Ibrahim, Muhammad Akmal (KnE Social Sciences, 2025)
This research examines the development of talent management studies within a volatile, uncertain, complex, and ambiguous (VUCA) context through an integrated bibliometric analysis and systematic literature review. Based on 231 publications from 2020 to early 2025, it identifies major patterns, thematic areas, cross-disciplinary links, and geographic trends shaping the field. The bibliometric review shows a notable increase in academic focus after the pandemic, influenced by the rising strategic role of talent management in digital changes, sustainability issues, and workforce robustness. Thematic analysis emphasizes transitioning from traditional HR practices to creating flexible talent networks, incorporating insights from business, social sciences, environmental studies, and information technology. The study also emphasizes an increasing contribution from developing nations, indicating the importance of adopting local-global talent strategies. Though comprehensive, the study recognizes limitations, such as excluding nonindexed sources and not conducting a detailed qualitative analysis. The results provide valuable insights for both researchers and practitioners seeking to develop resilient, sustainable, and adaptable talent management strategies suited to the complexities of today’s organizational environment.